Hypertonic saline solution and high dose of diuretic, ¿what do we know and how can we use them in persistent congestion? - Orozco Burbano, Juan D. (2021)
The presence of decompensated heart failure continues to be a condition with high rates of hospitalization, impact on the health system, and quality of life for those who suffer it. The mainstay of treatment in these cases are diuretics. However, the resistance to this pharmacological group may occasionally occur, generating an inadequate negative fluid balance and persistence of congestion with negative clinical outcomes. Hypertonic saline solution with high doses of diuretic emerges as a therapeutic option for this group of patients with probable physiological, and clinical benefits on hospitalization and re-admission rates due to heart failure decompensation. A review of the most relevant aspects and benefits of this combination is discussed in this article.